Quality of Synthetic Speech Perceptual Dimensions, Influencing Factors, and Instrumental Assessment - Hinterleitner, Florian; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book reviews research towards perceptual quality dimensions of synthetic speech, compares these findings with the state of the art, and derives a set of five universal perceptual quality dimensions for TTS signals. They are: (i) naturalness of voice, (ii) prosodic quality, (iii) fluency and intelligibility, (iv) absence of disturbances, and (v) calmness. Moreover, a test protocol for the efficient indentification of those dimensions in a listening test is introduced. Furthermore, several factors influencing these dimensions are examined. In addition, different techniques for the instrumental quality assessment of TTS signals are introduced, reviewed and tested. Finally, the requirements for the integration of an instrumental quality measure into a concatenative TTS system are examined.
Introduction -- Speech Synthesis -- Auditory and Instrumental Quality Evaluation Metrics -- Perceptual Quality Dimensions -- Influencing Factors on Perceptual Quality -- Instrumental Quality Assessment -- Requirements for the Integration of an Instrumental Quality Measure into a Concatenative TTS System -- Conclusions.
Keywords: Signal processing; User interfaces (Computer systems).; Human-computer interaction; Signal, Speech and Image Processing; User Interfaces and Human Computer Interaction